Mathematical programming applications in finance - Wang, Ganming (SPIE, 2023)
In the financial market, optimization is one of the most important goals for stakeholders to obtain. This essay focuses on some mathematical programming methods that applied in finance marketing to meet the aims of the financial market, introduces some concepts of mathematical programming and finance, and showcases the inter-relationship between these two subjects. This paper also provides examples of models that used linear programming method for solving asset pricing and liability cash flow matching scenario, initiates analysis from previous models by other scholars, and the defects of models using these methods. The demonstration of the non-linear programming method, to solving problems which is more complicated, for instance, in long-term scenario there will be the effect of economies of scale or random variables that are not predictable. This paper manifests a method of correcting linear programming models to match real-life scenarios better by adding quadratic programming constraints and illustrates some differences between linear programming and non-linear programming.